Pengaruh Customer Value terhadap Purchase Decision melalui Beauty Blogger di Youtube (Studi Pada Pelanggan Kosmetik Local Brand di Sumatera Selatan) - Dian Eka; Yulia Hamdaini (Program Studi Magister Manajemen FE Unsri, 2017)
Tujuan penelitian – This study is aimed to; First, to understand the significant effect of customer value on purchase decision through beauty blogger on Youtube. Second, to understand the influence of beauty blogger on Youtube significantly to purchase decisionDesain/Metodologi/Pendekatan – This study uses 200 respondents as sample. Structural Equation Modelling analysis is used to test the hypotheses.Temuan – The results are based on the regression assessment there is influence of customer value on purchasing decision through beauty blogger. Customer value also directly affects purchasing decision. Only beauty blogger has a significant directly effect on purchasing decision.Keterbatasan penelitian – The limitations of this study focus on viewers of beauty bloggers on youtube with customer value variables and cosmetic purchase decisions as the main variables.Originality/value – The originality of this article examines the effect of customer value, purchasing decisions after watching certain cosmetic brand reviews of beauty bloggers on youtube.